Enhanced meaning in life following psychedelic use: converging evidence from controlled and naturalistic studies - Roseby, William; Kettner, Hannes; Roseman, Leor; Spriggs, Meg J.; Lyons, Taylor; Peill, Joe; Giribaldi, Bruna; Erritzoe, David; Nutt, David J.; Carhart-Harris, Robin L. (Frontiers in Psychology, 2025)
IntroductionPsychedelics, such as psilocybin, are increasingly recognized for their propensity to elicit powerful subjective experiences that carry personal meaning. While research has demonstrated the capacity for these compounds to promote psychological wellbeing, it has yet to be shown to what extent they modulate "meaning in life", a specific contributor to mental and physical health.MethodsUsing the Meaning in Life Questionnaire (MLQ), we examined changes in meaning in life occurring across three different contexts of psychedelic use, including a randomized clinical trial of psilocybin for depression, controlled administration of psilocybin in a single-arm healthy volunteer study, and a naturalistic observational study following participants in psychedelic retreats. Meaning in life changes were analyzed with linear mixed models, and relationships to other predictors and outcomes were examined via Pearson correlations.ResultsAcross all contexts, the sub-factor “presence of meaning” was strongly increased after a psychedelic experience, while the sub-factor “search for meaning” was only weakly reduced. Enhancements of meaning in life were also moderately correlated with changes in measures of mental health, including mental wellbeing and depression severity. In line with previous research, we found that mystical, ego dissolution and emotional breakthrough experiences were correlated with an increase of meaning in life, with context-dependent differences in the strength of the association.DiscussionThe convergence of evidence from multiple studies shows that psychedelic use has a robust and long-lasting positive effect on meaning in life. We explore potential mechanisms of psychedelic-induced meaning enhancement and highlight the possible influences of psychosocial context on outcomes.